KEMAMPUAN TUMBUH PSEUDOMONAS PUTIDA STRAIN 071 PADA MEDIUM DIAZINON - Isna Rasdianah Azis (Teknosains, 2014)
Diazinon is an organophosphate pesticide used by farmers in increasing agricultural production because it's ability to control various pests. Excessive diazinon has potential as a pollutant in the environment. It residues are not soluble in water and difficult degraded. Also diazinon is toxic. This is a fatal effect on non target's body. This research aims to study and test the growth ability Pseudomonas putida strain 071  in medium containing 0.5% diazinon substrate. This study begins with the purification of Pseudomonas putida strain 071 isolates with scratch techniques. The growth ability tested through growth experiments using liquid basal medium containing 0.5% diazinon. Each interval of time, the growth observed using spectrophotometry (A = 620nm).The results obtained that the Pseudomonas putida 071 were able to grow in liquid basal medium containing diazinon. The splitting speed containing diazinon is 0.197 and 0,187 without diazinon. Generation time of Pseudomonas putida 071 use diazinon 5.2 hours and 5.4 hours without diazinon. Pseudomonas putida 071 that grow in liquid basal medium containing diazinon showed that diazinon residues can be used by this bacteria as a growth substrate. This bacteria has potential as pesticide degrading agents that can be used as a biopesticide active ingredients.